2020
DOI: 10.1016/j.jallcom.2019.152157
|View full text |Cite
|
Sign up to set email alerts
|

HRTEM analysis of the high-temperature phases of the newly developed high-temperature Ni-base superalloy VDM 780 Premium

Abstract: VDM 780 Premium is a recently developed Ni-based superalloy designed for working at high service temperatures (above 650 C) while keeping the good workability of alloy 718. VDM 780 Premium is based on the austenitic matrix (g phase) strengthened by intermetallic Ni 3 Al-like precipitates (g' phase, fcc L1 2 structure). Other co-precipitates may be formed in function of the applied heat treatment, such as Ni 3 Nb-based (d phase, orthorhombic DO a structure) or Ni 3 Ti-based (h phase, hexagonal DO 24 structure) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…This is so because the major reflections of both phases are very close, while the minor reflections are hard to detect given the relatively small amount of δ/η in the alloy. First TEM investigations on a small number of particles demonstrated the simultaneous presence of δ and η within one particle [41]. This fits to the observation made earlier in conjunction with Figure 6e and it appears likely that both phases coexist not only in VDM Alloy 780 but also in the model alloys studied here.…”
Section: The Effect Of the Al/ti Ratiosupporting
confidence: 91%
“…This is so because the major reflections of both phases are very close, while the minor reflections are hard to detect given the relatively small amount of δ/η in the alloy. First TEM investigations on a small number of particles demonstrated the simultaneous presence of δ and η within one particle [41]. This fits to the observation made earlier in conjunction with Figure 6e and it appears likely that both phases coexist not only in VDM Alloy 780 but also in the model alloys studied here.…”
Section: The Effect Of the Al/ti Ratiosupporting
confidence: 91%
“…In [8,21,22], a new Nb-containing wrought superalloy was developed. In this context, it was found that Co-addition increases the solvus temperature of the Nb-rich high temperature precipitates that were identified to consist of η-and δ-phase [23].…”
Section: Discussionmentioning
confidence: 99%
“…The microstructure at the room and elevated temperature of VDM 780 has already been investigated in previous publications by the authors of this paper by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM) as well as ND and SANS [26][27][28]. The microstructure consists of γ-matrix, hardening γ -phase, and high temperature stable δand η-phases.…”
Section: Introductionmentioning
confidence: 86%